2014
DOI: 10.4049/jimmunol.1302779
|View full text |Cite
|
Sign up to set email alerts
|

The Fli-1 Transcription Factor Regulates the Expression of CCL5/RANTES

Abstract: The Fli-1 transcription factor, an Ets family member, is implicated in the pathogenesis of systemic lupus erythematosus (SLE) in human patients and murine models of lupus. Lupus-prone mice with reduced Fli-1 expression have significantly less nephritis, prolonged survival and decreased infiltrating inflammatory cells into the kidney. Inflammatory chemokines, including CCL5, are critical for attracting inflammatory cells. In this study, decreased CCL5 mRNA expression was observed in kidneys of lupus prone NZM24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…In previous reports, we have demonstrated that a decrease of Fli‐1 in endothelial cells results in a significant reduction of expression levels, both mRNA and protein, of several inflammatory mediators . G‐CSF plays a role in the regulation of neutrophils and in patients with SLE a subset of the neutrophil population expresses increased inflammatory cytokines and cytotoxicity of endothelial cells .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In previous reports, we have demonstrated that a decrease of Fli‐1 in endothelial cells results in a significant reduction of expression levels, both mRNA and protein, of several inflammatory mediators . G‐CSF plays a role in the regulation of neutrophils and in patients with SLE a subset of the neutrophil population expresses increased inflammatory cytokines and cytotoxicity of endothelial cells .…”
Section: Resultsmentioning
confidence: 91%
“…Mutation of the third tryptophan abolishes DNA binding of Ets1 to the enhancer within Maloney sarcoma virus and mutation of this conserved amino acid abolishes binding of Fli‐1 to the Ets binding domain and reduces activity within the collagen α2(I) promoter . Increasing evidence has demonstrated that the Fli‐1 transcription factor is a key regulator of a number of inflammatory cytokines and chemokines , suggesting that Fli‐1 may be more important in inflammation than previously recognized. A critical role for Fli‐1 was demonstrated in the pathogenesis of SLE and the development of lupus nephritis .…”
Section: Introductionmentioning
confidence: 99%
“…MRL/lpr Fli1 +/+ immune cells, including T cells, do not readily migrate to the kidney when transferred into MRL/lpr Fli1 +/− mice (10). Chemokines Ccl2 ( Mcp-1 ), Ccl3 ( Mip-1α ), Ccl4 ( Mip-1β ) and Ccl5 ( Rantes ) are significantly decreased at the message level in the kidneys of MRL/lpr Fli1 +/− compared to Fli1 +/+ mice and FLI1 was demonstrated to regulate the promoter activity of several different cytokine genes in endothelial cells (8, 9, 12, 13). Here we demonstrated that the expression Cxcl9 and Cxcl10 , CXCR3 ligands, also are significantly decreased in the kidneys of MRL/lpr Fli1 +/− compared to the Fli1 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…The putative ETS sites in hCXCR3 tested for FLI1 binding were chosen based on numerous studies, including some from our laboratory, demonstrating that FLI1 binds and acts through conserved canonical ETS sites that are more proximal to the transcription start site (9, 12, 17, 3441). However, we recently demonstrated that FLI1 also can regulate promoters through more distal sites (12, 13). Alternatively, FLI1 may indirectly regulate Cxcr3 transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation